Socialism as a global alternative - Casanova, Pablo González (FCL-UNESP Laboratório Editorial, 2007)
Having as a background the crisis of the countries of a 'socialist orientation', the author of this paper tries to present a new globalizing socialist project, from what in the past was called Third World. As an example, he uses the Cuban experience of resistance to the capital as a step forward towards a democratic socialism.